2020
DOI: 10.1126/sciadv.aay4697
|View full text |Cite
|
Sign up to set email alerts
|

Global crotonylome reveals CDYL-regulated RPA1 crotonylation in homologous recombination–mediated DNA repair

Abstract: Previously, we reported that chromodomain Y-like (CDYL) acts as a crotonyl-coenzyme A hydratase and negatively regulates histone crotonylation (Kcr). However, the global CDYL-regulated crotonylome remains unclear. Here, we report a large-scale proteomics analysis for protein Kcr. We identify 14,311 Kcr sites across 3734 proteins in HeLa cells, providing by far the largest crotonylome dataset. We show that depletion of CDYL alters crotonylome landscape affecting diverse cellular pathways. Specifically, CDYL neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 43 publications
1
83
0
Order By: Relevance
“…For example, the SUMOylation of RPA1 increases its interaction with RAD51 and enhances DNA repair through HR ( 52 ). The acetylation of RPA1 by PCAF/GCN5 is critical for UV-induced nucleotide excision repair; while the lysine crotonylation (Kcr) of RPA1 regulated by CDYL promotes the interaction between RPA1 and ssDNA in response to CPT treatment ( 53 ). The ubiquitination of RPA2 by PRP19 promotes the recruitment and activation of ATR-ATRIP to DNA damage sites ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the SUMOylation of RPA1 increases its interaction with RAD51 and enhances DNA repair through HR ( 52 ). The acetylation of RPA1 by PCAF/GCN5 is critical for UV-induced nucleotide excision repair; while the lysine crotonylation (Kcr) of RPA1 regulated by CDYL promotes the interaction between RPA1 and ssDNA in response to CPT treatment ( 53 ). The ubiquitination of RPA2 by PRP19 promotes the recruitment and activation of ATR-ATRIP to DNA damage sites ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Kcr in non-histone proteins was originally identified in HeLa, A549, and H1299 cell lines, [12][13][14] and a recent crotonylome dataset established in HeLa cells identified 14 311 Kcr sites across 3734 proteins. [15] Some reports have also shown the presence of crotonylation in zebrafish, papaya, and rice. [16][17][18] These studies revealed that the whole proteomes exhibit substantially more complex temporal and spatial expression variability than do histones, suggesting that Kcr data must be collected from various species and tissues under different conditions for comprehensive characterization of the function of crotonylome.…”
Section: Doi: 101002/pmic202000049mentioning
confidence: 99%
“…Gene Ontology (GO) annotation proteome was derived from the UniProt-GOA The CREBBP and p300 proteins as well as PCAF and MOF catalyze the crotonylation on histones and non-histone proteins 3 . Crotonylation has been demonstrated to be involved transcription and DNA repair 3,4 . Though several proteomic studies have been focused on the regulation of crotonylation in cells [4][5][6] (1.5~2) and Q4 (>2).…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…Crotonylation has been demonstrated to be involved transcription and DNA repair 3,4 . Though several proteomic studies have been focused on the regulation of crotonylation in cells [4][5][6] (1.5~2) and Q4 (>2). Then each category was clustered according to KEGG analysis as it showed in Figure 1D.…”
Section: Bioinformatics Analysismentioning
confidence: 99%